2014
DOI: 10.1051/0004-6361/201423999
|View full text |Cite
|
Sign up to set email alerts
|

Probing the gas content of radio galaxies through H I absorption stacking

Abstract: Using the Westerbork Synthesis Radio Telescope, we carried out shallow H i absorption observations of a flux-selected (S 1.4 GHz > 50 mJy) sample of 93 radio active galactic nuclei (AGN), which have available SDSS (Sloan Digital Sky Survey) redshifts between 0.02 < z < 0.23. Our main goal is to study the gas properties of radio sources down to S 1.4 GHz flux densities not systematically explored before using, for the first time, stacking of absorption spectra of extragalactic H i. Despite the shallow observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 58 publications
5
55
0
Order By: Relevance
“…Our optical depth upper limit of τ < 0.004 is consistent with the stacking result by Geréb et al (2014), of τ < 0.002 for 66 sources (Fig. 5).…”
Section: Testing For a Statistical Detection In The Stacked Non-detecsupporting
confidence: 91%
See 1 more Smart Citation
“…Our optical depth upper limit of τ < 0.004 is consistent with the stacking result by Geréb et al (2014), of τ < 0.002 for 66 sources (Fig. 5).…”
Section: Testing For a Statistical Detection In The Stacked Non-detecsupporting
confidence: 91%
“…Their compact sources exhibited the broadest line features and were more often seen to have asymmetric lines. Geréb et al (2014) suggest that this trend in compact sources is due to the presence of unsettled gas, which is typically traced by asymmetric and redshifted/blueshifted lines. These properties point to interactions between the AGN and the circumnuclear medium in such compact galaxies -the feedback from the newly triggered AGN which is still propagating through this medium would be the cause of the unsettled gas.…”
Section: Disturbed Gas Kinematics In Compact Galaxiesmentioning
confidence: 99%
“…The H I profile is broader than that typically found in radio galaxies (Gereb et al 2014), but resembles what is observed in some other clusters; we discuss this in more details in Sect. 4.1.…”
Section: H I Gassupporting
confidence: 71%
“…However, the H I profile detected in 4C 35.06 appears to be broader than in typical radio galaxies (Gereb et al 2014). However, it resembles some of the profiles found in other clusters (in particular Abell 2597 and Abell 1795 mentioned above) that show relatively broad wings in the H I absorption profile, perhaps a signature of the more disturbed kinematics of the gas due to the cluster environment, as seen also in molecular gas by McNamara et al (2014) derived from ALMA data of Abell 1835.…”
Section: Presence Of Cold Gasmentioning
confidence: 89%
“…Several HI absorption surveys revealed that compact radio galaxies display a significant excess in the detection rate with respect to extended radio sources (Conway 1997;Morganti et al 2001;Pihlström et al 2003;Vermeulen et al 2003;Gupta et al 2006;Chandola et al 2011;Curran et al 2013;Geréb et al 2014).…”
Section: Absorptionmentioning
confidence: 99%